Morphology of the Developing Caecum and Colon and Histochemistry of the Developing Colon in Male Rabbits - Elnagy, Tahany M. MA.; Osman, Dafalla I. (Journal of Veterinary Medicine and Animal Production, 2021)
The objectives of the study were to investigate the histology and ultrastructure of the caecum and colon and histochemistry of the colon have been conducted on 50 Blanc de Bouscat male rabbits with ages varied between 0- 30 days. The investigation showed that the mucosa of the caecum and colon was composed of crypts with villar shape at 0-day of age and the length of the crypts decreased with advancing age. The crypts were lined by striated epithelial cells. Goblet cells were prominent. The absorptive columnar cells had apical microvilli and contained vacuoles of different size, ovoid to elongated nucleus, mitochondria, rough endoplasmic reticulum and lateral membranous interdigitations. Cells with polymorphic secretory granules were noticed. Varying degrees of positive reaction to PAS diastase resistant material and diastase- digested material (glycogen) was found in the colon.